Canine mast cell tumors: diagnosis, treatment, and prognosis - Garrett LD (Dove Medical Press, 2014)
Laura D Garrett Department of Veterinary Clinical Medicine, University of Illinois College of Veterinary Medicine, Urbana, IL, USA Abstract: Mast cell tumors (MCTs) are the most common malignant skin cancer in dogs, and significant variability exists in their biological behavior. Most MCTs are cured with appropriate local therapy, but a subset shows malignant behavior with the potential to spread to lymph nodes, liver, spleen, and other areas and to thus become a systemic cancer. Because of this variable behavior, it is difficult to predict how any individual tumor is going to behave. The variability thus creates uncertainty in deciding what a particular dog's prognosis is, whether staging tests to assess for metastasis are needed, and even what treatments will be necessary for best outcome. In addition to controversies over the potential for development of systemic disease, or diffuse metastasis, controversies also exist over what treatment is needed to best attain local control of these tumors. This article will briefly discuss the diagnosis of MCTs in dogs and will summarize the literature in regards to the controversial topics surrounding the more aggressive form of this disease, with recommendations made based on published studies. Keywords: mitotic index, mastocytosis, tyrosine kinase inhibitor, histologic grade